Integer Programming and Combinatorial Optimization : 19th International Conference, IPCO 2017, Waterloo, ON, Canada, June 2628, 2017, proceedings /: 19th International Conference, IPCO 2017, Waterloo, ON, Canada, June 2628, 2017, proceedings. (2017) - Unknown
No abstract available